Collins International Primary Maths Workbook 4 - Wrangles , Paul; Clissold ,Caroline (Collins : London, 2016)
Collins International Primary Maths supports best practice in primary maths teaching, whilst encouraging teacher professionalism and autonomy. A wealth of supporting digital assets are provided for every lesson, including slideshows, animations, tools and games to ensure they are rich, lively and engaging. Each Workbook page has three levels of challenge which allow learners to practise and consolidate their newly acquired knowledge, skills and understanding of the mathematics they are learning. Provides support as part of a set of resources for the Cambridge Primary curriculum framework from 2011. This title is endorsed by Cambridge Assessment International Education.